1973
DOI: 10.1161/01.cir.47.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Left Ventricular Contraction in the Systolic Click Syndrome

Abstract: Left ventricular (LV) shape change during systole was characterized in nine patients with typical clinical findings of the systolic click syndrome (SCS) by means of cineangiographic measurements of three segmental diameters of the LV cavity and of the mitral valve ring (MVR) and contrasted with findings in eight patients with normal LV function. In the latter group, shortening of the proximal, midventricular, and apical segment diameters was comparable, averaging 38.6, 40.3, and 46.8%, respectively; MVR shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Regional variations in shortening were first detected in humans by Kong et al (12) using coronary bifurcations as surface markers during coronary angiography. These investigators, and Liedke et al (17), by using angiographic techniques, showed greater shortening at the apex compared with the base of the LV. With dimension gauges implanted at the midwall in the direction of the midwall myofibers, shortening was found to be greatest in the apex (ϳ20%) and less at the midwall and base of the ventricle (16).…”
Section: Regional End-systolic Strains and Effects Of Afterloadmentioning
confidence: 82%
“…Regional variations in shortening were first detected in humans by Kong et al (12) using coronary bifurcations as surface markers during coronary angiography. These investigators, and Liedke et al (17), by using angiographic techniques, showed greater shortening at the apex compared with the base of the LV. With dimension gauges implanted at the midwall in the direction of the midwall myofibers, shortening was found to be greatest in the apex (ϳ20%) and less at the midwall and base of the ventricle (16).…”
Section: Regional End-systolic Strains and Effects Of Afterloadmentioning
confidence: 82%
“…Techniques such as contrast left ventriculography (Liedtke et al, 1973;Sniderman et al, 1973;Bove et al, 1978;Gelberg et al, 1979;Klausner et al, 1982;Sheehan et al, 1983) and echocardiography (Shapiro et al, 1981;Haendchen et al, 1983) demonstrate considerable nonuniformity of the contraction process. However, these techniques a priori impose a certain level of uniformity on the contraction process by presuming that different endocardial sites will all move along a perpendicular pathway to a common long axis, or along a prescribed radial pathway to a common center of mass.…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly interested in the minor axis level because several indices of systolic function estimate the amount of circumferential shortening at this level by measuring the resultant shortening of an internal diameter, radius, or minor axis chord. Although considerable nonuniformity of contraction has been demonstrated by techniques such as left ventriculography (Liedtke et al, 1973;Sniderman et al, 1973;Bove et al, 1978;Gelberg et al, 1979;Klausner et al, 1982;Sheehan et al, 1983), echocardiography (Shapiro et al, 1981;Haendchen et al, 1983) and fluoroscopic tracking of midwall markers (Ingels et al, 1980(Ingels et al, , 1981, these methods do not directly measure regional circumferential shortening, but rather infer this from the resultant motion which occurs perpendicular to the assumed major direction of shortening.…”
mentioning
confidence: 99%
“…Thus, in anesthetized dogs, sectional FAC, WTh and shortening increased from left ventricular base to apex as follows: 39.4 ± 5.1% to 61.6 ± 7.2%, 20.5 ± 6.6% to 46. 7 11.5% and 22.7 ± 3.4% to 35.4 5.9%, respectively. Similar trends were noted in conscious dogs.…”
mentioning
confidence: 88%